1999
DOI: 10.1080/08990229970366
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of experimental pruritus and mechanically evoked dysesthesiae in an area of cutaneous allodynia

Abstract: We investigated the effects of tactile allodynia on the itch and mechanically evoked dysesthesiae produced by an intradermal injection of histamine in human volunteers. After an intradermal injection of capsaicin into the volar surface of one forearm, there developed an area of tactile allodynia to stroking and hyperalgesia to pricking the skin. Histamine was then injected simultaneously into the area of allodynia (experimental arm) and into the opposite forearm (control arm). Magnitude estimates of itch were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 7 publications
7
53
1
4
Order By: Relevance
“…Experimental itch and accompanying dysesthesiae were enhanced by a local anesthetic ) and attenuated in hyperalgesic skin surrounding a capsaicin injection ). These studies demonstrated functional interactions between pruritic and nociceptive neural systems and lend support to the hypothesis that the mechanisms subserving itch are inhibited centrally by mechanisms that underlie pain and hyperalgesia Brull et al 1999;Graham et al 1951;Nilsson et al 1997;Ward et al 1996).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Experimental itch and accompanying dysesthesiae were enhanced by a local anesthetic ) and attenuated in hyperalgesic skin surrounding a capsaicin injection ). These studies demonstrated functional interactions between pruritic and nociceptive neural systems and lend support to the hypothesis that the mechanisms subserving itch are inhibited centrally by mechanisms that underlie pain and hyperalgesia Brull et al 1999;Graham et al 1951;Nilsson et al 1997;Ward et al 1996).…”
Section: Introductionmentioning
confidence: 60%
“…Another property expected of a candidate pruriceptive neuron in the CNS is that its activity is inhibited by algesic stimuli applied to normal skin and by the development of algogenic dysesthetic states such as allodynia and hyperalgesia (Bickford 1938;Brull et al 1999;Graham et al 1951;Koppert et al 1993;Nilsson et al 1997;Ward et al 1996). Rather than being inhibited by capsaicin, most of the STT neurons in the present study were vigorously excited, after which they became sensitized to stroking and to punctate stimuli.…”
Section: Neuronal Response Properties That Might Contribute To Itch Amentioning
confidence: 70%
“…Electrical stimulation at levels sufficient to induce pain also can reduce itch (Bickford 1938;Nilsson et al 1997;Ward et al 1996). Finally, application of the pain-inducing chemical capsaicin reduces histamine-induced itch in humans (Brull et al 1999). These findings suggest that many forms of noxious stimulation can reduce itch.…”
mentioning
confidence: 84%
“…It is also noteworthy that noxious stimulation such as scratching, heat, cold, and capsaicin suppresses or relieves itch (Bickford, 1937;Ward et al, 1996;Weisshaar et al, 1998;Brull, 1999;Yosipovitch et al, 2005). Although the precise mechanisms are not known, it is generally accepted that nociceptive signals inhibit incoming itch signals by central mechanism (Bickford, 1937;Brull et al, 1999;Yosipovitch et al, 2005). Therefore, this central inhibitory effect of nociceptive signals on itch input in part explains why capsaicin evokes pain predominantly although it is highly likely to excite both nociceptors and pruritic sensory fibers.…”
Section: Discussionmentioning
confidence: 99%